A wideband flexoelectric energy harvester based on graphene substrate. (15th March 2021) - Xue, Jiangtao; Chen, Lihua; Chang, Liqi; Zhang, Wei
Highlights: A graphene-based vibration energy harvester is designed to reduce energy loss. The working frequency band is widened by collision of the two beams. Analytical model is established to predict the flexoelectric energy harvester performance. Effect of collision is analyzed under different external frequency. Effects of the parameters on performance of the energy harvester are analyzed. Abstract: High efficiency and wide bandwidth are the main optimization directions for energy harvester. Based on flexoelectric theory, this paper presents a micro cantilever vibration energy harvester (VEH) with a broad bandwidth which achieved by collisions of two beams. The nanocrystalline graphene (NCG) is selected as base layer because its quality factor ( Q factor) is highest compared with common materials, which means its energy loss in progress of power conversion is lowest and device has a high sensitivity to external excitation. Considering flexoelectric effect, based on Hamilton's principle and Hertz contact force model, the electromechanical coupling equations are obtained. Numerical simulations are conducted. Output voltages of upper and lower beam are calculated respectively and the frequency response curve of the power density is obtained. It has been found that the maximum output voltage of flexoelectric energy harvester is almost 5 times that of piezoelectric energy harvester when the thickness of substrate layer is 400 nm. The effects of some parameters, such as resistance, gap distance between two beams, and tip mass, on the performance of harvester are studied. It indicates that the working bandwidth of the VEH has increased approximately fourfold, and the output power density is improved in some case due to collision of two beams, which has been verified by experiment. This work designs a novel efficient micro VEH and provides a theoretical basis for structure optimization.